2021
DOI: 10.1101/2021.07.28.454242
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TREM2 interacts with TDP-43 and mediates microglial neuroprotection against TDP-43-related neurodegeneration

Abstract: Triggering receptor expressed on myeloid cell 2 (TREM2) is a surface receptor that, in the central nervous system, is exclusively expressed on microglia. TREM2 variants have been linked to increased risk for neurodegenerative diseases, but the functional effects of microglial TREM2 remain largely unknown. To this end, we investigated TAR-DNA binding protein 43 kDa (TDP-43)-related neurodegenerative disease via viral-mediated expression of human TDP-43 protein (hTDP-43) in neonatal and adult mice or inducible e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 89 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…The Trem2 -/line was kindly provided by Dr. Marco Colonna at the Washington University School of Medicine, St. Louis, and was bred at Mayo Clinic (Xie et al, 2022a). Wild type mouse line was purchased from Jackson Laboratory.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Trem2 -/line was kindly provided by Dr. Marco Colonna at the Washington University School of Medicine, St. Louis, and was bred at Mayo Clinic (Xie et al, 2022a). Wild type mouse line was purchased from Jackson Laboratory.…”
Section: Animalsmentioning
confidence: 99%
“…As a cell surface receptor, TREM2 is expressed exclusively in microglia (Colonna and Wang, 2016) in the central nervous system (CNS), macrophages (Do et al, 2022) and dendritic cells (DCs) (Bouchon et al, 2001) (Ulland and Colonna, 2018). The deficiency of TREM2 impairs the ability of microglia to sense and degrade numerous antigenic materials, including but not limited to pathogens (N'Diaye et al, 2009), apoptotic neurons (Takahashi et al, 2005), β-amyloid (Wang et al, 2015;Wang et al, 2016;Zhao et al, 2018), TAR DNA binding protein 43 (TDP-43) (Xie et al, 2022a), myelin (Cantoni et al, 2015), and neuronal synapses (Scott-Hewitt et al, 2020). Early studies reported that upon ligation of TREM2, genes related to MHC class II rapidly upregulate (Bouchon et al, 2001).…”
Section: Introductionmentioning
confidence: 99%